Effect of Elastic Contact Force on Tribological Characteristics of Current-carrying Roll Rings in Rotating Conductive Joints. Issue 1 (2nd January 2023) - Chen, Tianhua; Song, Chenfei; Liu, Zili; Wang, Li; Sun, Chao; Pang, Xianjuan; Zhang, Yongzhen
Abstract: A novel rotating conductive joint consisting of an inner raceway, an outer raceway, and an elastic ring was proposed in this study. The elastic ring was clamped between the inner and outer raceways using elastic compression force. The effect of the elastic force on the current-carrying properties and the damage of the ring material was investigated. As the elastic force increased from 10.2 N to 20.4 N, the total frictional force decreased from 15.5 N to 9.5 N, and the contact resistance decreased from 0.37 Ω to 0.18 Ω. While monitoring the revolution and rotation of the elastic ring, it was observed that the slip-rolling ratio decreased from 43.04% to 31.74%. Furthermore, a low friction coefficient was obtained under a high elastic force, which could be attributed to the small slip-roll ratio. The scanning electron microscopy and optical microscopy results revealed that a low friction coefficient led to subsurface crack initiation and a low degree of grain deformation. When the friction coefficient at a single contact point was greater than 0.34, fatigue occurred directly on the contact surface. The high friction-induced plastic deformation could cause surface hardening. Therefore, a high friction coefficient and large surface fatigue did not lead to high wear at low elastic forces.